PENGEMBANGAN BAHAN AJAR MEMBACA PEMAHAMAN BERDASARKAN STRATEGI PLAN (PREDICT, LOCATE, ADD, NOTE) UNTUK SISWA KELAS VII - Sudiati, Sudiati; Nurhidayah, Nurhidayah (LITERA, 2017)
Abstract This study aims to produce reading comprehension learning materials based on the PLAN strategy and to find out the appropriateness for Grade VII students. This was a design and development study. The stages were taken from those of Borg and Gall. The data were qualitative and quantitative in nature. The data trustworthiness was assessed in terms of credibility, transferability, dependability, and confirmability. The research instruments were an interview guide and a questionnaire. The data were analyzed by the qualitative technique and descriptive statistics. The research product is a reading comprehension course book consisting of an introduction, contents, and a supplement. The results of the evaluation by the the materials expert and the learning expert show that the developed course book is good in terms of content appropriateness, presentation, language, and graphics. These are indicated by a mean score of 3.78 from the the materials experts and 3.80 from the the learning expert. Keywords:learning materials, reading comprehension, PLAN strategy